Diatom community response to an episodic release of hazardous industrial organic chemicals - Lauren A. Schroeder; Colleen E. McLean (Academia Environmental Sciences and Sustainability)
A serious toxic chemical spill occurred in East Palestine, Ohio, USA, when 38 cars of a Norfolk Southern Train derailed and spilled hazardous industrial organic chemicals including vinyl chloride, 2-butoxyethanol, 2-ethylhexyl acrylate, isobutylene, butyl acrylate, and benzene into a small stream, Sulfur Run, in a sub-watershed of the Ohio River, killing thousands of fish and other aquatic organisms. Benthic diatoms were sampled 92 days after the spill, on May 17 2023, as a surrogate to assess water quality and evaluate the ecological resilience of diatoms to an episodic organic chemical spill. Diatom community metrics included non-metric multidimensional scaling (NMS) ordination, Multiple Response Permutation Procedures (MNPP) statistics, predominant diatoms, diatom water quality indices, trophic state, and diversity. Despite 92 days of recovery and “stream clean-up” measures, all metrics of diatom community structure in Sulfur Run, the polluted stream, and Leslie Run downstream from the confluence of Sulfur Run, remained statistically significantly different (lower quality) than in Leslie Run above the Sulfur Run confluence. Although the differences were relatively subtle, their high significance and range across a spectrum of diatom community metrics lend credence to the conclusion that the chemical spill caused alterations in the diatom community and support the contention that the effect on the diatoms was structural, i.e., affecting species composition rather than productivity. The study demonstrates the value of diatoms in assessing environmental impacts and confirms their potential for monitoring water quality restoration from episodic hazardous organic chemical spills.